Small-Scale Spatial Variability of Plant Nutrients and Soil Organic Matter: An Arable Cropping Case Study. Issue 19 (27th October 2016) - Qiu, Weiwen; Curtin, Denis; Johnstone, Paul; Beare, Mike; Hernandez-Ramirez, Guillermo
ABSTRACT: Soil properties can vary spatially due to differences in topography, parent material, and land management practices. For site-specific management within the field, information on spatial variation of soil properties is essential. This case study was conducted to quantify the spatial variability of available plant nutrients and organic matter under arable cropping in New Zealand. Within a 10.4-ha paddock that had a long-term history of arable cropping, 91 samples (0–7.5 cm) were collected in a grid pattern for determination of mineral nitrogen (Min N), anaerobically mineralizable N (AMN), Olsen P, total carbon (TC), and total N (TN). The data were evaluated using geostatistical and classical statistical methods. Although the paddock had a flat topography and had been managed uniformly for many years, nutrient concentrations exhibited substantial variability. All measured variables except mineral N showed moderate positional dependence. Autocorrelation distances were 400 m for Olsen P, 293 m for AMN, and 347 m for TC. Soil C showed a strong, positive correlation with the amount of clay plus fine silt (<5 µm fraction) and a negative correlation with sand content. These results suggest that textural variation was a major factor influencing within-field variability in soil organic matter. Using the spatial data, zones with different plant nutrient requirements were identified (four for N; two for P). An application strategy that accounts for fertility differences between zones may improve fertilizer use efficiency and contribute to better environmental outcomes; P inputs could be reduced by 50% by avoiding application to the high Olsen P zone.